Investigation of Mechanical and Thermal Properties of Waste EPDM and Polypropylene Mixtures - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2018)
Automotive sector was considered as a sector since polypropylene was often used with ethylene propylene diene monomer (EPDM) as a mixture. EPDM rubber is characterized by wide range of applications. The aim of this study is to investigate the reusability of EPDM wastes. 10, 20, 30, 40 and 50 wt% ground EPDM powders were mixed with polypropylene (PP) matrix by extrusion method. Test specimens were prepared out of those mixtures by injection moulding. Tensile, the Izod impact, hardness, density, heat deflection, and the Vicat softening point tests were performed on the specimens. Tensile strength, force at break, E modulus, hardness, heat deflection and the Vicat softening temperature values decreased with the increasing ground EPDM content in polypropylene matrix. However, the Izod impact and elongation at break values increased.
Keywords: RUBBER